Diaprepes Root Weevil on Southern Highbush Blueberry in Florida - Douglas A. Phillips; Oscar E. Liburd; Larry W. Duncan (EDIS, 2019)
Citrus root weevil, Diaprepes abbreviatus (Linnaeus) is a destructive pest on citrus trees. It is now becoming a significant pest on blueberry in central Florida, at times causing major damage to blueberry bushes that are more than two years old. This 3-page fact sheet written by Douglas A. Phillips, Oscar E. Liburd, and Larry W. Duncan and published by the UF/IFAS Entomology and Nematology Department will educate blueberry growers on how to monitor, identify, and control citrus root weevil. http://edis.ifas.ufl.edu/in1241